Globalization and social development after Copenhagen: Premises, promises and policies - Thandika Mkandawire; Virginia Rodríguez (United Nations Research Institute for Social Development (UNRISD), 2000)
This paper explores the social, economic and ideological context within which the World Summit for Social Development took place. As its subtitle implies, the discussion focuses particularly on some of the assumptions about global trends that were prevalent in 1995 and evaluates their adequacy in the light of the actual course of events during the following five years. The Summit was conceived during a period when neoliberal orthodoxy was at its height. Many countries were-willingly or unwillingly-implementing structural adjustment policies, devised by the Bretton Woods institutions (BWIs), that systematically weakened earlier national development strategies. The public was insistently reminded that, in the much-quoted words of Margaret Thatcher, there was no alternative to the free-market revolution. The collapse of the Soviet Union lent force to that assumption. The neoliberal case against earlier models of economic development and social welfare was further strengthened by growing reference to the process of 'globalization', which was seen not as the (reversible) outcome of particular national policies, but as an inevitable fact of contemporary economic life. This justified a broad attack on the welfare state, and indeed on many less comprehensive forms of public social provision that were assumed to be unviable in a highly competitive international marketplace. Notions of equity and social justice became unfashionable. A second feature of the period leading up to the Social Summit was the standardization of economic policy prescriptions, applied across a large part of the developing world. The 'fundamental' to which these prescriptions were tethered was not growth, but stabilization; and in most cases they worsened both poverty and inequality. But international financial institutions used the spectacular economic performance of a number of Asian countries (the so-called Asian miracle which, by 1995, was well into its second decade) to argue that neoliberal insistence on free markets was entirely justified. A third element in the climate of ideas surrounding the Summit was therefore a serious ongoing debate about the extent to which successful Asian economies did, in fact, epitomize free-market principles. Sceptics noted that the state in these countries played a major role in protecting and promoting national industries. Fourth, the mid-1990s were a time when renewed economic growth outside Asia seemed just around the corner. Economic statistics were looking healthier than they had in years. And the rapid surge of private financial flows toward some developing countries further supported a sense of optimism. How has this environment changed over the last five years? At the ideological level, neoliberalism is today far more contested than it was at the time of the Summit. Erosion of the theoretical and empirical underpinnings of the model has been accompanied by growing political opposition. The collapse of important Asian economies in 1997 dealt a serious blow to those who believed uncritically in rapid financial liberalization. And slow growth continued to afflict the majority of developing countries throughout the remainder of the decade. Indeed, in a sample of 95 developing economies monitored in the 1990s, 32 experienced declining per capita income in 1999, compared to only 14 in 1996. Five years after the Social Summit, poverty and inequality continue to grow, and prospects that this trend will be reversed remain quite poor. Continuing emphasis on austerity does not create the conditions for broad-based growth and social development. Unemployment and underemployment are increasing in many parts of the world. Moreover, the quality of work and working conditions is declining, under the impact of 'flexible' labour policies and the expansion of the informal sector. Private financial flows have not proved a panacea, either. They are concentrated in relatively few developing countries and, when significant, imply serious risk of greater economic volatility. Given this generally sombre picture, it is not surprising that poverty alleviation now occupies a central place on the development agenda. The World Bank has begun to justify support for social sectors on developmental grounds, and the IMF has been forced to recognize the importance of addressing social concerns. But there is still a tendency to deal with these issues in technocratic ways. Thus a single-minded focus on poverty reduction, without broader commitment to improving the quality of life throughout society, obscures issues of income distribution and social equity. In addition, targeting resources only toward the poorest or toward certain groups encourages the creation of a dual structure of social services-one aimed at the poor, funded by the state, and one aimed at the rest of the population, which can afford to pay for private services. This is not only poor politics, but also poor economics. In fact, neoliberal economics has traditionally denounced targeting in the economic field, citing problems of imperfect information, fundamental distortion of incentives, moral hazard, high administrative costs and corruption. Market orthodoxy is based on an ideal of non-intervention. Thus it is paradoxical that while universalism is championed in economics, it is roundly rejected in social policy. In another significant reversal of previous policies, the Bretton Woods institutions now concede a much more important role for the state. But this concession comes after years during which there has been a devastating weakening of state capacity. There is therefore a danger that states in parts of the developing world will now be expected to do too much-often in association with a trend to place ever more stringent conditions on delivery of loans or grants. The debt relief programme for heavily indebted poor countries, known as the HIPC initiative, clearly reflects this problem. Countries still struggling under the weight of inappropriate structural adjustment policies are required to assume anti-poverty commitments for which both resources and institutional capacity may be insufficient. Finally, recent years have witnessed attempts to rethink global governance and to create a more stable international economic environment. In most cases, however, this seems a patchwork affair. Suggestions for remedial action are tacked onto a system that is not being fundamentally analysed or challenged. If real progress is to be made, questions of distributive justice and social policy must become an integral part of the debate on development-not an add-on to be considered when existing economic policies prove inadequate.
Keywords: 330